Till skydd mot skada - En teoretisk systematisering och en praktisk prövning av intresse- och skadebegreppen vid kriminalisering - Sterner,Viktor (2016)
As much as members of society need to conform their conduct to the penal law, the state should also have to adhere to the penal law, by providing clear guidelines for when such law can be used. Such a guideline is that criminalization may serve to prevent harm to legally-recognized interests. This thesis aims to explore the concept of harm within the deliberations that attach to the criminalization process. The definition of harm that is given in this thesis, also embraces the concept of legally-protectable ”interests”, which is why the concept of interests is also adressed. The essay intends to highlight the gap that exists between the theory and practice of criminalization. Therefore, the final and concluding chapter of the essay contrasts the theory and practice of criminalization, demonstrated through the crimes of adult incest and bestiality. The first part of this thesis’ purpose, to identify the basic concepts of harm and interest, is being adressed in two sections, where each of the concepts are investigated separately. These sections together can be said to form a web, which can be used to determine the legitimacy of criminalization. A variety of theories, Swedish as well as Anglo-Saxon, are described and examined in two part-analyzes. Based on these analyzes, a systematization of existing theory on the concepts of harm and interests is undertaken, in order to illustrate their concealed meaning. As an overall conclusion, it is postulated that the concept of interest should be defined free from violations, and that the concept of harm in meaningful ways oppresses the discussion concerning the justification for criminalization. The status of the interest, before and after a violation, is the important part, as is the relatively neglected discussion on criminalization as ultima ratio. The latter idea is found to be important because the balancing process – in the essay appearing necessary when looking at the deliberations that inhere to criminalization – to a large extent is influenced by the idea of crimi-nalization as a last resort. In order to answer the second part of the thesis’ purpose, a review of the rationale behind the criminalization of adult incest and bestiality is attempted. A brief historical review is given in this section alongside a more comprehensive recitation detailing the emergence of the established law. In the last section, the theories are confronted with reality. An analysis is made of the applicability of the theories to concrete cases, together with an analysis of how criminalization of these two crimes relates to the standards that are devoloped in the concept sections of this thesis. The results show a gap between theory and reality, in that many of the theories prove difficult to apply in practice, as well as it is doubtful wheter legislation of the crimes analyzed can be justified under the standards imposed on the state, when it resorts to criminalization of conduct.
Keywords: Straffrätt; Criminal law; Rättsvetenskap; Law